2012
DOI: 10.1088/0022-3727/45/45/455301
|View full text |Cite
|
Sign up to set email alerts
|

Capacitance transient study of a bistable deep level in e-irradiated n-type 4H–SiC

Abstract: The energy needed to conduct the transformations were determined to E A (A → B) = (2.1 ± 0.1) eV and E A (B → A) = (2.3 ± 0.1) eV, respectively. The pre-factor indicated an atomic jump process for the opposite transition A → B and a charge carrieremission dominated process in case of B → A. Minority charge carrier injection enhanced the transformation from configuration B to configuration A by lowering the transition barrier by about 1.4 eV. Since the bistable FB-center is already present after low-energy elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 31 publications
0
16
0
1
Order By: Relevance
“…The upward bending of the left side tail of the peak for the lowest two correlators suggest the presence of the Ti(h) defect at approximately E c -0.12 eV; however, its peak was not observed in the temperature range used. Peak #2 is the Z 1/2 center which appears in all 4H-SiC samples and has been strongly correlated to carbon vacancies as established by several annealing studies using DLTS and EPR [74][75][76]. Theoretical calculations and EPR measurements suggest that the identity of the three levels could be the (−2/0) transition of the cubic and (−1/0) transition of both the cubic and hexagonal site carbon vacancies [72,73,76,77].…”
Section: Thermally Stimulated Current (Tsc) Measurementsmentioning
confidence: 65%
“…The upward bending of the left side tail of the peak for the lowest two correlators suggest the presence of the Ti(h) defect at approximately E c -0.12 eV; however, its peak was not observed in the temperature range used. Peak #2 is the Z 1/2 center which appears in all 4H-SiC samples and has been strongly correlated to carbon vacancies as established by several annealing studies using DLTS and EPR [74][75][76]. Theoretical calculations and EPR measurements suggest that the identity of the three levels could be the (−2/0) transition of the cubic and (−1/0) transition of both the cubic and hexagonal site carbon vacancies [72,73,76,77].…”
Section: Thermally Stimulated Current (Tsc) Measurementsmentioning
confidence: 65%
“…Beyer et al has also detected similar defect level (E c À 1.07 eV) in 2.5 MeV electron irradiated 4H-SiC. 38 EH 5 defect has been found in ion irradiated 4H-SiC and has been attributed to a carbon cluster. 31 The activation energy of Peak #5 was found to be 1.30 eV.…”
Section: Dlts Analysismentioning
confidence: 69%
“…This will be further supported by the thermal evolution of the defect population below. Moreover, electron irradiation experiments with energies below and above the Si displacement threshold [34,35] have shown that EH 4,5 only appear when V Si is created. Therefore, the Si vacancy is likely to be involved in their formation.…”
Section: B Correlating the C Si V C Defect And The Eh 45 Trapsmentioning
confidence: 99%